The HOME Study: Understanding How College Students at a Hispanic Serving Institution Coped with Food Insecurity in a Pandemic - Miriam Manboard (MDPI AG, 2021)
College students represent a unique population of adults, who may be more likely to experience food insecurity due to their transient circumstances, limited access to resources, and increased educational expenses. But little is known about how college students and their households mitigate food insecurity, particularly during a crisis like the COVID-19 pandemic. The Household Observations of Meals and Environments (HOME) Study described how college students in the US utilized multilevel resources, including an on-campus food pantry, to maintain food security during the pandemic. A convenience sample of college students (n = 18) were recruited from an on-campus food pantry and provided quantitative and qualitative data through online surveys and in-depth Zoom interviews. Survey data were analyzed to describe sociodemographic characteristics. In-depth interviews were recorded, transcribed, coded, and analyzed thematically to identify emergent themes. Social support and the use of an on-campus food pantry were primary factors in maintaining a food security safety net. Students faced barriers when trying to access federal and state food assistance programs and identified multilevel resources, their food security, and the role of social support as facilitators in their perceptions of food insecurity status and experiences. Findings highlight practical implications for research related to on-campus food insecurity interventions and policies to support food security among college students.